Numerical modeling of porous ceramics microstructure - Miedzińska, Danuta (Technical Sciences, 2019)
The presented research is directed to the porous ceramics microstructural behaviour assessment with the use of numerical methods. Such new material can be used for thermal insulation, filters, bio-scaffolds for tissue engineering, and preforms for composite fabrication. One of the newest and most interesting applications, considered in this work, is a usage of those materials for production of proppants for hydraulic fracturing of shale rocks. The hydraulic fracturing is a method of gas recovery from unconventional reservoirs. A large amount of fracturing fluid mixed with proppant (small particles of sand or ceramics) is pumped into the wellbore and its pressure causes the rock cracking and gas release. After fracturing the fluid is removed from the developed cracks leaving the proppant supporting the fracture. In the paper the grain porous ceramics which is used for proppant particles preparation was studied. The influence of grains distribution on the porous ceramics mechanical behaviour during compression was simulated with the use of finite element method.